Hygroscopicity of freeze-dried guava powder - Carvalho, Roberto F. de; Cal-Vidal, José (Pesquisa Agropecuaria Brasileira, 2014)
The hygroscopic behavior of freeze-dried guava (Psidium guajava L.) powder was studied considering the kinetics of water sorption in several environmental conditions of relative humidity (25%, 50%, 75% and 100%) and temperature (10°C, 25°C, 40°C and 55°C). From the obtained data, the heat of adsorption was estimated and, by using the Caurie equation (1970), the optimal level of humidity for the maximum product stability was determined.